2015
DOI: 10.1088/1748-9326/10/6/064009
|View full text |Cite
|
Sign up to set email alerts
|

Energy for water and water for energy on Maui Island, Hawaii

Abstract: Energy and water systems are interconnected. This work first characterizes 2010 primary energy demand for direct water services and local freshwater demand for energy on Maui Island, Hawaii, then investigates scenarios for future changes in these demands. The goal of this manuscript is to dissect the relationship and trends of energy-water connections to inform policymaking decisions related to water and energy planning. Analysis proceeds by inventorying water and energy flows and adjusting to a 2010 base year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Comanagement of energy and water resources is becoming increasingly important as challenges such as extended drought, climate change, and population growth add pressure to freshwater resources, especially in water-constrained regions. Recent historic droughts in California, Texas, and other parts of the southwestern US have drawn attention to water provisioning for energy-related uses, as well as farming and direct human consumption. ,, Water constraints have not been limited to drought-prone regions: even relatively water-rich regions have faced water-related energy curtailments over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Comanagement of energy and water resources is becoming increasingly important as challenges such as extended drought, climate change, and population growth add pressure to freshwater resources, especially in water-constrained regions. Recent historic droughts in California, Texas, and other parts of the southwestern US have drawn attention to water provisioning for energy-related uses, as well as farming and direct human consumption. ,, Water constraints have not been limited to drought-prone regions: even relatively water-rich regions have faced water-related energy curtailments over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Per capita WrE consumption for the industrial sector was observed within the range of 27 MJ/capita (in Spain based on material flow analysis) (Hardy et al, 2012) to 26,900 MJ/capita (in the USA based on material flow analysis) (Sanders and Webber, 2012). While for the agriculture sector it was 4 MJ/capita (in Delhi, India based on material flow analysis) (Ramaswami et al, 2017) to 9,762 MJ/capita (in Maui Island, Hawaii, USA based on material flow analysis) (Grubert and Webber, 2015).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 87%
“…Each power plant is mapped to the particular attribution boundary of interest. The data within the Chini et al, 27 Bartos and Chester, 38 DeNooyer et al, 39 Grubert and Webber, 40 EIA are self-reported via Form 923 and come with their own sets of uncertainty (although data quality has improved markedly in recent years 32 ). Quantifying the uncertainty of the underlying reported data has been evaluated by others 12,32 and is outside the scope of this study.…”
Section: ■ Backgroundmentioning
confidence: 99%